Low-energy electron beam sterilization of solid alginate and chitosan, and their polyelectrolyte complexes. (1st June 2021) - Farno, Maylis; Lamarche, Camille; Tenailleau, Christophe; Cavalié, Sandrine; Duployer, Benjamin; Cussac, Daniel; Parini, Angelo; Sallerin, Brigitte; Girod Fullana, Sophie
Graphical abstract: Highlights: Low-energy electron beams are valuable sterilization techniques for porous polysaccharidic networks. Continuous beam irradiation lead to less depolymerization of alginate or chitosan alone. PEC formation has a protective effect against degradation under irradiation. Optimal settings of pulsed irradiation were found to sterilize PEC scaffolds. Low-dose (<25 kGy) may be sufficient to sterilize 3D architectured polysaccharidic materials. Abstract: Polysaccharidic scaffolds hold great hope in regenerative medicine, however their sterilization still remains challenging since conventional methods are deleterious. Recently, electron beams (EB) have raised interest as emerging sterilization techniques. In this context, the aim of this work was to study the impact of EB irradiations on polysaccharidic macroporous scaffolds. The effects of continuous and pulsed low energy EB were examined on polysaccharidic or on polyelectrolyte complexes (PEC) scaffolds by SEC-MALLS, FTIR and EPR. Then the scaffolds' physicochemical properties: swelling, architecture and compressive modulus were investigated. Finally, sterility and in vitro biocompatibility of irradiated scaffolds were evaluated to validate the effectiveness of our approach. Continuous beam irradiations appear less deleterious on alginate and chitosan chains, but the use of a pulsed beam limits the time of irradiation and better preserve the architecture of PEC scaffolds. This work paves the way for low energy EB tailor-made sterilization of sensitive porous scaffolds.